Motives for information gathering, learning and online technology engagements of small and medium tourism enterprises in kerala - Tintumol P. Joseph, Ms; ArunPrem, Mr; Merlin Thanga Joy, Dr (International Journal of Engineering and Technology, 2018)
Considerable differences are acknowledged with regard to the nature of information, use of information and source of information between commercially oriented and non-commercially oriented SMTEs. While commercially, groups are more active in to the formal tourism forums and engage more with online source of information, non-commercially group are satisfied with the current learning environment and they are keener in making satisfied customers. However, both group seeks less information related to legal rather they concentrate more on fetching information related to marketing, sales, finance, and management. The present study is an attempt to gain insights upon the motives that drive small and medium tourism enterprises, understand the desired information and learning process needed to develop business, and to know the online Technology engagements in the development of business.Â Â